Economics by design : - Collinge, Robert A. (Prentice Hall, 1999)
Using a unique modular format, this up-to-date survey presents current issues and core principles of mainstream economics in an intuitive manner that captures reader interest. It systematically combines this presentation with a wealth of relevant, up-to-date applications drawn from today's professional world. Discuss cover such timely issues as the World Bank; the International Monetary Fund; the International Labor Organization; economic growth; short-term instability; production, growth, and trade; political prices and elasticity; the international marketplace; the public sector; market failure; taxation and public choice; employment, output, and fiscal policy; and more. For those interested in any/all facets of mainstream economics.